CHINA’S ROLE IN THE UNITED NATIONS IN ADDRESSING CLIMATE CHANGE DURING THE XI JINPING ERA - Shabirah, Sarah; Setiawan, Ari Putra; Oktavianto, Fajar; Albiansyah, Alif; Saputro, Dedy (BHUVANA: Journal of Global Studies, 2025)
Climate change has become a critical global challenge in the 21st century, with China as the largest emitter playing a vital role in addressing it. This research aims to analyze China’s transforming role within the UN framework in addressing climate change during Xi Jinping’s era, focusing on diplomatic posture changes and policy implementation. Using qualitative research methods with a descriptive-analytical approach through library research, this study analyzes various official documents, journal articles, and policy reports from 2020-2024. The discussion reveals that under Xi Jinping’s leadership, China has undergone a significant transformation from a defensive position to proactive leadership in global climate diplomacy, reflected through its 2060 carbon neutrality commitment and the establishment of a 3 billion USD South-South Climate Cooperation Fund. Analysis through an offensive realist perspective reveals that China’s active engagement in the global climate regime manifests a power maximization strategy in the international system. In conclusion, China’s transforming role has positively contributed to global climate governance while maintaining its national strategic interests through a combination of ambitious commitments and various policy instruments.